Business Process Re-Engineering and Its Effective Impact on Job Performance in South Refineries Company - Khdair, Wameedh A. (South Asian Journal of Social Sciences and Humanities, 2021)
The aim of the research is to know the effect that the business process re-engineering had on the performance of employees of the south refineries company – Iraq. With the addition of some observations that contribute to leaving a good impact for the purpose of seeking to develop the concept of engineering for workers. As the results were relied upon to conduct analyzes through SPSS statistical analysis program on the 350 employees in the company. The results indicated a set of concepts and indications, the most important of which are the application of the engineering concept was present in the company at a rate of 60% and the existence of a direct relationship between the dimensions of business process re-engineering and the level of job performance. The purpose of the research See the relationship between HR aspects, such as teamwork, management competency, organizational structure, IT and efficient communication for achieve beneficial outcomes by reducing costs, time and increasing productivity for determining the level of business process re-engineering in the south refineries company, southern Iraq. From the viewpoint of its employee such as knowing the level of guest performance for people working in the south refineries company, identify the strength of the relationship between the company’s employees and the engineering management, and determining the level of business process re-engineering in the south refineries company.